Studi Kasus Neoplasia Limpa dan Hati Anjing Shih Tzu dengan Pemeriksaan Klinis dan Ultrasonografi - Iman, Bintang Nurul; Murtiningrum, Fitria Senja; Rahmiati, Dwi Utari; Gunanti, Gunanti; Noviana, Deni (Jurnal Veteriner; Vol 23 No 3 (2022)DO - 10.19087/jveteriner.2022.23.3.352, 2023)
Disorders of the spleen and liver are cases that are quite common in dogs, especially in old age. Ultrasonography (USG) of the abdomen is one of the diagnostic imaging tools to determine the changes and severity of disease in the hepatobiliary visceral organs and spleen. A 12-year-old, unneutered male Shih Tzu dog weighing 5 kg had clinical symptoms of vomiting, weakness, and a pain response when palpated in the abdomen. The examination was carried out at the VTH SVMBS IPB University. Abdominal ultrasound examinations were routinely performed every month from November 2021 to March 2022. The results obtained from a series of ultrasound examinations for five months showed that the size of the hypoechoic nodule in the spleen did not change significantly with dimensions of length x width x height of about 1.1 x 0. 8 x 1 mm. The texture of the liver parenchyma is not homogeneous in all lobes. Hypoechoic nodules were seen in all lobes of the liver. A Significant increase in the size of the nodules was observed in the left lobe liver in the second month of examination and did not change in the following month. Hematological examination of the blood showed that the dog had thrombocytosis and granulocytosis. The results of the blood chemistry examination showed that ALP and ALP levels tended to increase at each assessment. The conclusion is the dog was diagnosed with neoplasia in the spleen and liver